(untitled) (Bangladesh Journal of Medical Science, 2026)
Background and Objective Visfatin is a new adipocytokine primarily released by adipose tissue. It showed to affect both lipid and glucose metabolism and contribute to the chronic inflammatory condition associated with obesity. This study aimed to determine visfatin levels in obese and non-obese adult males and investigate their relationship with selected metabolic markers including insulin resistance and lipid profile. Materials and Methods Blood specimens were taken from 90 adult males categorized into two groups: obese and non-obese. Biochemical parameters were measured, including visfatin concentrations by using an enzyme-linked immunosorbent assay (ELISA) with a human visfatin ELISA kit, FBG, lipid profile, and hs-CRP using the Cobas 6000 c501 system, and FI using the Cobas 6000 c601 system. Results Serum visfatin levels were significantly elevated in obese subjects. FI, FBG, lipid profile, hs-CRP, HOMA-IR, and DBP are also significantly elevated in obese group. Visfatin showed a significant positive correlation with BMI, WC, FI, FBG, lipid profile, hs-CRP, HOMA-IR, and DBP, but a significant negative association with HDL-C. Conclusion The findings suggest that serum visfatin levels are markedly increased in obesity and are strongly linked with both insulin resistance and dyslipidemia. These results support the potential of visfatin as a predictive biomarker of metabolic dysregulation in obese individuals. BJMS, Vol. 25 No. 02 April’26 Page: 602-608